THE USE OF SOCIAL MEDIA FOR PHARMACISTS’ PROFESSIONAL ACTIVITIES IN UNITED ARAB EMIRATES: A DESCRIPTIVE STUDY - IBRAHIM, OSAMA MOHAMED; IBRAHIM, RANA; AL-TAMEEMI, NOOR KIFAH; RILEY, KAREN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of this study is to assess the perception of patients and pharmacists in the United Arab Emirates about social media uses in health-care delivery. Methods: A cross-sectional survey was distributed among patients and pharmacists residing in Dubai, Sharjah and Abu Dhabi. Their perception of social media uses in delivering health-care services was evaluated by analyzing their attitude toward the benefits and associated risks of social media. Results: The survey study had a total of 267 participants, including 150 patients and 117 pharmacists. Based on the results, 69.2% of the pharmacists agreed that social media, text message, or e-mail can be effectively used by them to improve patient communication. For patients, the study showed that the greatest percentage (77.3%, n=116) utilize both: Disease-related information and information on drugs. About 69.2% of pharmacists chose WhatsApp to be the most used platform, and 60.7% of patients prefer using Instagram as a health-care platform. Conclusion: The use of professional development tools for social networking is likely to continue to evolve. Integrating social media with the practice of pharmacy and patient care will have a positive impact on achieving optimal patient care.